Confronting epidemics three case studies: SARS, AIDS, Influenza - Garner, Simon; Baden-Powell, Edwina; Video Education Australasia (Australia : Video Education Australasia, 2004)
This program examines modern day epidemics, using three case studies from the late 20th and early 21st centuries - SARS, HIV-AIDS, and Influenza
Title from title screen
Executive producer, Mark McAuliffe
Senior secondary
DVD Format
Keywords: Epidemics; SARS (Disease); AIDS (Disease); HIV (Viruses); Influenza